Design of Outseal PLC-Based Temperature and Humidity Regulator for Oyster Mushroom Cultivation Rooms Using Node-RED - Jujung Caesar Ningearso Putra; Rini Puji Astutik (G-Tech: Jurnal Teknologi Terapan, 2025)
Oyster mushroom is one type of exotic plant that has high economic value and great potential to be developed commercially. The current economic condition of mushroom cultivation is not supported by the availability of adequate investment capital and limited human resources in the oyster mushroom sector. In addition, oyster mushroom cultivation requires special skills and supporting technology. Increasingly developing technology provides more choices in technology development, especially in the field of oyster mushroom cultivation. PLC Outseal is one alternative in the development of oyster mushroom cultivation technology. PLC Outseal was chosen because it is cheap and has been proven reliable in the industrial world. Controlling room temperature 22 - 28 ℃ and humidity 60 - 80% in oyster mushroom cultivation is very important for the success of oyster mushroom cultivation. In this study, the use of the LM35 sensor with ladder plc outseal programming has an error of 1.3% when compared to the HTC-1 digital thermometer and the humidity sensor has an error of 0.69% when compared to the SM150T. The use of RS 485 in communication up to 110 m between slaves has no obstacles and is very stable in testing between slave plc outseal. Node RED as an IoT (Internet of Things) platform is very good for monitoring the temperature and humidity of the growing media in mushroom cultivation.